2020
DOI: 10.1111/jbi.13812
|View full text |Cite
|
Sign up to set email alerts
|

Island‐biogeographic patterns of spider communities on epiphytes depend on differential space use among functional groups

Abstract: Aim: Positive relationships between island size and species richness have been found for oceanic and non-oceanic islands. However, the effect of isolation, also predicted by island-biogeographical theory, seems challenging to test. Species-specific mechanisms drive the perception of distance and space for animals, and therefore isolation patterns are masked when described at the community level. We used epiphytic plants (canopy islands) and their spider communities to study how functional group and species-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Despite the prevalence of spiders in tropical canopies, we are unaware of any studies that have quantified the mechanisms influencing canopy-spider community assembly after rainforest conversion into cash-crop monoculture plantations. However, it has been demonstrated that tree canopy openness and vegetation complexity, for example, coverage by herbs, shrubs and epiphytes, affect local spider communities (Méndez-Castro et al, 2020;Méndez-Castro et al, 2018;Stenchly et al, 2011;Zheng, Li & Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the prevalence of spiders in tropical canopies, we are unaware of any studies that have quantified the mechanisms influencing canopy-spider community assembly after rainforest conversion into cash-crop monoculture plantations. However, it has been demonstrated that tree canopy openness and vegetation complexity, for example, coverage by herbs, shrubs and epiphytes, affect local spider communities (Méndez-Castro et al, 2020;Méndez-Castro et al, 2018;Stenchly et al, 2011;Zheng, Li & Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Spiders are one of the most ubiquitous and diverse taxa in terrestrial ecosystems (Coddington & Levi, 1991). These arthropods are useful for understanding how dispersal and habitat interact (Florencio et al, 2016;Gavish & Ziv, 2016;Malumbres-Olarte et al, 2014), and in the field of insular biogeography, they are providing evidence of how isolation, mobility and microhabitat size affect the functionality of species and assemblages (Méndez-Castro et al, 2020) as well as colonisation and vicariance processes across archipelagos (Čandek et al, 2019;Gillespie, 2002;Rominger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Spiders are one of the most ubiquitous and diverse taxa in terrestrial ecosystems (Coddington & Levi, 1991). These arthropods are useful for understanding how dispersal and habitat interact (Florencio et al, 2016; Gavish & Ziv, 2016; Malumbres‐Olarte et al, 2014), and in the field of insular biogeography, they are providing evidence of how isolation, mobility and microhabitat size affect the functionality of species and assemblages (Méndez‐Castro et al, 2020) as well as colonisation and vicariance processes across archipelagos (Čandek et al, 2019; Gillespie, 2002; Rominger et al, 2015). Furthermore, spiders can be used to understand the effects of dispersal, between‐habitat differences and disturbance on the SADs of assemblages, providing useful information for conservation management (Boieiro et al, 2018; Borges et al, 2008; Cattin et al, 2003; Kaltsas et al, 2019; Kondratyeva et al, 2019; Leroy et al, 2014; Morel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The variables used for tree selection were tree height (T‐I = 14.8 m, T‐II = 14.8 m, T‐III = 12.6 m), stem diameter at breast height (T‐I = 0.52 m, T‐II = 0.51 m, T‐III = 0.59 m), and canopy cover—estimated from the largest crown radius—(T‐I = 4.3 m, T‐II = 6.2 m, T‐III = 7.8 m). Further details are reported in Méndez‐Castro et al (2018, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Since epiphytes are the main habitat used by different canopy‐dwelling animals (Cruz‐Angón et al, 2009; Cruz‐Angón & Greenberg, 2012), their heterogeneous spatial distribution within trees can be expected to promote a heterogeneous distribution of their associated‐fauna. After the colonization of epiphytes, various mechanisms such as environmental filters, competition, predation, or dispersal limitation (Méndez‐Castro et al, 2018, 2020) can determine the spatial distribution of animals within the epiphyte habitat of each tree. If these mechanisms do not have a significant role, the spatial distribution of the associated fauna is expected to simply follow that of the epiphytic habitat.…”
Section: Introductionmentioning
confidence: 99%